Efficient emission modelling in lean premixed flames with pre-tabulated formation characteristics. (1st October 2021) - Chen, Zhang; Yang, Tianwei; Zhang, Shanshan; Li, Shan; Ren, Zhuyin
Highlights: The NOx and CO formation characteristics in thin reaction zone have been investigated. The small-scale turbulence is quantified in preheat zones of 1-D premixed flames. An efficient emission modelling approach has been formulated and demonstrated. The fuel/air unmixedness is important for the quantitative NOx prediction. Abstract: It is practically important to accurately predict NOx and CO emissions in lean premixed flames for the development of fuel-efficient and low-emission combustion systems. In this study, the efficient modelling with pre-tabulated formation characteristics of NOx and CO is systemically investigated. Their formation characteristics for turbulent flames in the flamelet and thin reaction zone regimes are first quantified with one-dimensional adiabatic premixed flames through the incorporation of turbulence induced diffusion. Results show that the formation of NOx and CO can be characterized by two different stages, i.e., a rapid increase of both in flame front and the linear growth for NOx and exponential decay for CO in post-flame zone. An efficient NOx and CO modelling approach is formulated and demonstrated in a full-scale methane gas turbine combustor, in which species NOx and CO are transported and solved, with the source terms being modelled by pre-tabulated formation characteristics from one-dimensional premixed flames with detailed chemical kinetics. Realizable k-epsilon model and finite rate/eddy dissipation model in conjunction with a two-step global mechanism are employed to primarily predict the flow and flame characteristics. Results show that the predicted NOx and CO agree with experimental measurements over a wide range of equivalence ratios. The discrepancy in NOx emission can be accounted by fuel/air unmixedness. For CO, the rapid increase due to the incomplete CO oxidation resulting from its increasing characteristic oxidation time near lean blow-out (LBO) is correctly captured. It is further shown that the predicted CO emission is sensitive to combustion/kinetics model parameters and the accurate prediction of flame shape and dynamics is crucial to capture the trend of CO formation near LBO.